Sports injuries among adolescents: incidence, causes and consequences - Schneider, Sven; Yamamoto, Shelby; Weidmann, Christian; Brühmann, Boris A. (Journal of paediatrics and child health, 2012)
Aim: The purpose of this study was to evaluate the 1-year incidence, location, type, mechanism and severity of sports injuries for adolescents in Germany. Methods: Data were from the ‘German Health Interview and Examination Survey for Children and Adolescents’, a nationwide study of n = 17 641 children and adolescents. Analyses were based on a weighted total sample size of nw = 7451 adolescents between 11 and 17 years of age, 51% of them boys. Results: A total of 577 adolescents (8%) reported having experienced a sports injury during the past year. Collisions and falls were reported as being the most important causes. The most frequent diagnoses were contusions, dislocations, strains and sprains (60%), followed by fractures (26%). Most injuries (88%) were treated on an outpatient basis with only 12% resulting in hospitalisation. Gender-specific analyses showed that 9% of the boys and 7% of the girls suffered from a sports injury during the past year. After adjusting for the level of physical activity, these gender differences disappeared (ORgirls 0.94; 95% confidence intervals: 0.74-1.18). Excluding injuries incurred from falls while horse riding, there were no gender differences in the mechanism of injury. Among boys, 30% of all injuries were fractures, among girls 20% (P < 0.05). Apart from fractures, no further differences between the sexes in the range of diagnoses were identified. Conclusions: Although these results suggest that the risk of sports injuries does not differ significantly based on adolescents' gender, the incidence rate of adolescent sports injuries within Germany is relatively high.